Доброто, убавото и вистината во Платоновата филозофија - Наумоска, Јасмина (Филозофски факултет, Скопје, 2016)
The ancient concept of “good and beautiful” in Plato’s philosophy gets a wider scope by adding the category of “truth”. The introduction of the category of “truth” within the concept of καλοκἀγαθία is considered to have been first articulated in Plato’s philosophy. This article aims to draw out the theoretical implications of this specific triple concept and to elaborate on it in a broader philosophical context. In that sense, the link between “good” and “beautiful” will be analyzed in a few places in Plato’s dialogues where they are explicitly compared (e.g. “Symposium” 201c, 204de; “Protagoras” 359e-360b), and later associated with the concept of “truth” (especially in “Philebus” 64e-65a, together with the category “proportion”). Through this analysis, it will be shown that the ideal of καλοκἀγαθία in Plato’s philosophy, with its connection to the concept of truth, has strong metaphysical foundations. The text will pose the questions of the ontological relation between these three categories (the possibility of hierarchization, the good beyond the beautiful and the truth), and the possibility of their unification in erotic desire. Their relationship will be examined as a basis for a good life, mainly referring to “Philebus”, while reaffirming the fundamental ontological problem of χωρισμός.
Keywords: Plato, good, beautiful, truth, χωρισμός